Market Dynamics in Diverging Economies: A Comparative Study of the MERVAL and S&P 500 Indices - Yacoubian, Leandro Jorge; Ketenchian, Grigor Sahak; Carvalho, George Harrison Ferreira de; Merdinian, Kevin (Revista JRG de Estudos Acadêmicos, 2022)
This paper investigates the co-movement between the Argentine MERVAL index and the U.S. S&P 500 from January 2019 to January 2022, a period marked by intense global financial volatility and domestic macroeconomic instability in Argentina. Using a dataset of monthly adjusted closing prices, we compute percentage changes and assess the degree of correlation through both Pearson and Spearman coefficients. Our results indicate a moderate yet statistically significant relationship between the two indices, suggesting that Argentina’s stock market is partially integrated with global trends but still exhibits strong idiosyncratic behavior. Periods of global shocks tend to synchronize the indices, while domestic crises lead to divergence. The findings are discussed in light of previous literature on financial contagion, emerging market integration, and volatility transmission. This study contributes to understanding the asymmetrical dynamics of financial markets in diverging economies and highlights the relevance of context-specific modeling when assessing risk and performance in emerging equity markets.